PEMBELAJARAN TEMATIK-EKSPLORATIF-DEMOKRATIS DALAM FISIKA MELALUI EKSPLORASI PENGALAMAN EMPIRIK MAHASISWA TENTANG AIR - Muya, Angelika Birene; Silangen, Patricia Merdiana; Makahinda, Tineke; Tumangkeng, Jeane; Lahope, Kenny Setiawan (LPPM Politeknik Saint Paul Sorong, 2024)
Thematic-Exploratory-Democratic Learning (TED-L) is an instructional strategy that encourages students to engage in high-level thinking through exploring objects around them and democratic interactions. The aim of this study is to investigate: 1) The outcomes of exploring the physics context-concepts from students' empirical experiences themed around water in TED learning, and 2) How students' democratic interactions contribute to exploring the physics context-concepts from empirical experiences in TED learning. This research employs interpretative qualitative research methodology and data analysis using Miles and Huberman's model. It is part of a collaborative research comprising 3 stages out of the 6 overall stages of TED Learning: 1) Building TED Attraction Literacy, 2) Object Exploration, 3) Exploring individual learning attitudes and democratic learning attitudes. The findings of this study are: 1) Examining empirical experiences leads to a process of high-level thinking formed as an attempt to solve problems. 2) Democratic interactions enhance students' creativity, increase analytical levels, and foster critical thinking among learners, as well as boost engagement in exchanging and adding new information related to physics concepts in exploring empirical experiences.